Az átmenet etikája – Az előregyártott síremlék, mint önkép - Csaba TÓDOR (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2021)
The Ethics of Transition – The Prefabricated Tombstone as Identity Portrait. The present paper is part of a broader study. The broader context of the re-search compares and analyses the English and Transylvanian funeral rituals. My current paper examines a slice of this broader research context, identifying the problem of the funeral ritual, which has traditionally served as a transitional and linear ceremony. As such, the funeral started to transform from being a transi-tional ritual into a mosaic, personalized rite, by losing its transitional character. In the context of examining the social causes, the study examines how linear transitional elements are eliminated in funerals and, ultimately, how so-called existential holes appear in the funeral rituals.